ANALISIS KINERJA BANK SEBELUM DAN SESUDAH MERGER & AKUISISI DENGAN METODE ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) - Toto Rahardjo; Himmiyatul Amanah Juwa Juwita; Risna Wijayanti (Universitas Katolik Widya Karya Malang, 2020)
Merger and acquisition activities can influence financialperformance. Observation about the impact appearing beforeand after the activities is required. The objective of this studyis to identify and evaluate the financial performance ofcompanies based on EVA and MVA values. This descriptiveresearch is a study on go-public banking companies listed inthe Indonesia Stock Exchange that have carried out mergerand acquisition activities during the period of 2011-2014.After selecting the samples, PT Bank Permata Tbk., PT BankRakyat Indonesia Tbk., and PT Bank Tabungan PensiunanNasional Tbk. are used as the object of the research. Theresults show that positive and increasing EVA value can beachieved by maximizing acquisition of operational profit andreducing capital cost, as shown by PT Bank Rakyat IndonesiaTbk. before and after the acquisition. Positive and increasingMVA value is achieved from the value of equity market that ishigher than that of deposited equity capital. Positive MVAvalues are shown by all samples (PT Bank PermataTbk., PTBank Rakyat Indonesia Tbk., and PT Bank TabunganPensiunan Nasional Tbk.).